Identificação e caracterização de metodologias e atividades ativas nos cursos de graduação da UFVJM - Fernandes, Geraldo Wellington Rocha; Monteiro, Nathália Lages; Souza, Giovana Silva Figueiredo (Revista Vozes dos Vales: Publicações Acadêmicas, 2019)
The active approach of teaching-learning process in university graduate courses stands out as an effective tool in the solid construction of knowledge. In contradiction, studies about it are scarce and its results and applicability are unknown. In this context, this review seeks to identify and characterize the methodologies and active activities registered in the Pedagogical Projects of university graduate Courses of Universidade Federal dos Vales do Jequitinhonha e Mucuri (UFVJM) in Diamantina (MG). So, a documentary search was conducted in search of keywords, which contains the main methodologies and active activities addressed in 33 PPCs available on the UFVJM website. It was identified a total of four technologies covered by 17 PPCs and eight active activities described in 32 PPCs. It was identified a total of four active methodologies addressed by 17 PPCs and eight active activities described in 32 PPCs. It was verified that not all the projects present indications of active methodologies, that the most cited refers to the methodology of case study and teaching cases. For active activities, there are highlights for study groups, seminars, workshops and thematic debates. It was concluded that it is not the goal of pedagogical projects to adapt to the active teaching-learning proposal and that there are still difficulties to its better dissemination.